'What is puberty, then?' Smartphones and Tumblr images as de/re-territorialisations in an upper secondary school classroom. Issue 6 (2nd November 2019) - Paakkari, Antti; Rautio, Pauliina
ABSTRACT: In this paper, we explore the part mobile phone use plays in the capitalist assemblages present in school classrooms. Capitalism is approached through the continuous movement of de- and re-territorialisation. The empirical grounding is a wide study on mobile phone use conducted at an upper secondary school in Finland. The focus of this paper is one psychology lesson on puberty and the ways in which territories such as puberty are challenged in the school life of young people through their mobile phone use in class. Analysing a student's Tumblr photo stream, we show how smartphones challenge the existing territorialities in a classroom. We locate three central deterritorialising movements: in relation to the physical space of the classroom; to the affective space of the classroom; and to the notion of body in puberty. We conclude that mobile phone use matters to students intimately and channels flows of capitalism at school.